2007
DOI: 10.1021/om7004904
|View full text |Cite
|
Sign up to set email alerts
|

First Examples of Diazepanylidene Carbenes and Their Late-Transition-Metal Complexes

Abstract: The synthesis of the novel seven-membered N-heterocyclic carbene (NHC) 1,3-dicyclohexyl-1,3diazepan-2-ylidene (3) and its 5,6-dioxolane derivative 4 is reported and their coordination chemistry with Rh(I), Ir(I), and Pt(0) discussed. The M(cod)(3)Cl, where M ) Rh and Ir, complexes display a high rotation barrier at room temperature about the M-C NHC bond, whereas for the M(CO) 2 ( 3)Cl and Pt-(nbe) 2 (3) complexes rapid rotation of the carbene ligand is observed at ambient temperature. The infrared ν(CO) value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 51 publications
(47 reference statements)
10
83
1
2
Order By: Relevance
“…In addition, increasing the ring size to six- [39e] and sevenmembered carbenes [47] results in an increased electron richness (Table 4, entries 38, 43, and 48; the formulas for 22 and 23 are shown in Figure 10). In addition, abnormal pyridylannulated carbene 27 (Table 4, entry 45) reported by Lassaletta and co-workers, is remarkably more electron donating as a ligand (D(TEP) = À5.8 cm À1 ) than the corresponding "normal" NHC imidazol[1,5-a]pyridine-3-ylidene (25) ( Table 4, entry 23).…”
Section: Variation Of the Electronic Properties By Appropriate Choicementioning
confidence: 99%
“…In addition, increasing the ring size to six- [39e] and sevenmembered carbenes [47] results in an increased electron richness (Table 4, entries 38, 43, and 48; the formulas for 22 and 23 are shown in Figure 10). In addition, abnormal pyridylannulated carbene 27 (Table 4, entry 45) reported by Lassaletta and co-workers, is remarkably more electron donating as a ligand (D(TEP) = À5.8 cm À1 ) than the corresponding "normal" NHC imidazol[1,5-a]pyridine-3-ylidene (25) ( Table 4, entry 23).…”
Section: Variation Of the Electronic Properties By Appropriate Choicementioning
confidence: 99%
“…However, despite the correspondence of Edn with the TEP in many cases, the moderate Edn value calculated for the structure 54H draws attention since its TEP index was the lowest found experimentally (2029.2 cm -1 ). 256 The high value of Edn calculated for the yet unknown mesoion 54G (80.0 Kcal / mol) is also noteworthy (Scheme 54).…”
Section: 251mentioning
confidence: 92%
“…In this sense, it has been demonstrated that small modifications to the NHC ligands may lead to drastic changes in their σ-donor properties, stability, or steric constraints, all of which allow fine-tuning of the properties of the metal center. The most commonly exploited modifications of NHC ligands include ring size, ranging from five to seven atoms, 10,11 changes to the location of the carbon atom, 12 and the substituents appended to the nitrogen atoms. Among the modifications described above, we considered the latter one for the specific purpose of introducing groups at the imidazole N-positions to access sterically hindered, functionalized substituents.…”
Section: Introductionmentioning
confidence: 99%